2015
DOI: 10.5812/archcid.20991
|View full text |Cite
|
Sign up to set email alerts
|

The Frequency of imp and vim Genes Among Pseudomonas aeruginosa Isolates From Children’s Medical Center of Tehran

Abstract: Background:The first report of Pseudomonas aeruginosa ( P. aeruginosa ) carbapenem resistant strains, and especially the Metallo-BetaLactam (MBL) producers was from Japan, however, further reports were global. Objectives: The current study aimed to determine the frequency of vim and imp genes among P. aeruginosa MBL producer isolated from Children Medicinal Center during from 2011 to 2012. Materials and Methods: In the current descriptive study, 90 P. aeruginosa strains were collected from different clinical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
3
2
Order By: Relevance
“…In the present study, similar to several studies in Iran, bla VIM and bla IMP have been only carbapenemase genes that were identified in carbapenem-resistant isolates of P. aeruginosa [ 3 , 16 , 17 ]. Also, our study, was not in agreement with Hakemi Vala et al and Bagheri Bejestani studies in Tehran, Iran, that reported no bla VIM positive P. aeruginosa isolates from different clinical samples such as burns’ patients [ 18 , 19 ]. However, bla VIM rates vary greatly among different studies [ 16 19 ] which may reflect differences in infection control policies and other factors.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…In the present study, similar to several studies in Iran, bla VIM and bla IMP have been only carbapenemase genes that were identified in carbapenem-resistant isolates of P. aeruginosa [ 3 , 16 , 17 ]. Also, our study, was not in agreement with Hakemi Vala et al and Bagheri Bejestani studies in Tehran, Iran, that reported no bla VIM positive P. aeruginosa isolates from different clinical samples such as burns’ patients [ 18 , 19 ]. However, bla VIM rates vary greatly among different studies [ 16 19 ] which may reflect differences in infection control policies and other factors.…”
Section: Discussioncontrasting
confidence: 97%
“…Also, our study, was not in agreement with Hakemi Vala et al and Bagheri Bejestani studies in Tehran, Iran, that reported no bla VIM positive P. aeruginosa isolates from different clinical samples such as burns’ patients [ 18 , 19 ]. However, bla VIM rates vary greatly among different studies [ 16 19 ] which may reflect differences in infection control policies and other factors.…”
Section: Discussioncontrasting
confidence: 97%
“…In our study, 1.9% of the imipenem non-susceptible isolates of P. aeruginosa carried VIM-type MBLs. Bagheri Bejestani et al reported that bla VIM gene was not detected among the studied isolates in the center of Iran (27). However, several previous reports revealed that the genes of bla IMP and bla VIM -type MBL are often encoded on mobile genetic cassettes, which can easily spread among isolates.…”
Section: Discussionmentioning
confidence: 90%
“…Most samples were clinical urine specimens. Only MBL-associated genes including IMP and VIM were evaluated, 3.3% and 0%, respectively [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…In only one of these studies, the positivity rate of VIM gene was above 50%, and in other studies, it was between 0% and 47%. The frequency rate of imp gene was thoroughly various, between 0% and 100% [ 4 , 9 , 11 , 12 , 16 , 21 , 23 , 25 , 45 – 55 ].…”
Section: Discussionmentioning
confidence: 99%